2003
DOI: 10.1016/s0886-3350(03)00065-8
|View full text |Cite
|
Sign up to set email alerts
|

Implantable contact lens for moderate to high myopia

Abstract: Central and/or peripheral contact between the ICL and the crystalline lens may be responsible for the high incidence of ASCC formation in this study. Central vaulting greater than 0.09 mm appears to protect the crystalline lens from cataract formation. However, we recommend aiming for higher central vaulting (0.15 mm) to avoid contact between the ICL and the crystalline lens. This should be attainable by implanting longer ICLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(79 citation statements)
references
References 13 publications
3
76
0
Order By: Relevance
“…The distance between the center of the posterior artificial lens surface and the center of the anterior crystalline lens surface (referenced as vault) [5] plays an important role in the occurrence of complications after ICL implantation surgery. If the vault value is insufficient or the separation between the intraocular and the human lens is short, the risks of anterior subcapsular cataract would be high [6,7,8]. On the other hand, an excessive vault will cause pupillary block and/or anterior angle closure that may result in secondary glaucoma [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The distance between the center of the posterior artificial lens surface and the center of the anterior crystalline lens surface (referenced as vault) [5] plays an important role in the occurrence of complications after ICL implantation surgery. If the vault value is insufficient or the separation between the intraocular and the human lens is short, the risks of anterior subcapsular cataract would be high [6,7,8]. On the other hand, an excessive vault will cause pupillary block and/or anterior angle closure that may result in secondary glaucoma [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In centers using ICL implantation shortly after introduction of phakic lenses, subcapsular anterior opacities were observed [10][11][12][13][14][15] within and apart the optical axis. Decreased light transmittance of the crystalline lens was found by fluorophotometry, 16 continuously increasing for 27 months, 17 but anterior subcapsular opacities and decreased light transmittance did not always develop in parallel.…”
mentioning
confidence: 99%
“…However, there is not always a correspondence between white-to-white and sulcus-to-sulcus, and indeed, it differs greatly between individuals. If a large-diameter lens is inserted, crystalline lens opacification tends not to occur [10], and did not occur with our 13.5-mm lens, but IOP elevation and effects on corneal endothelial cells remain a concern [2].…”
Section: Discussionmentioning
confidence: 77%
“…In Japan, a clinical trial of ICL (Staar Surgical, USA), a posterior chamber type of phakic IOL that can be inserted through a small corneal incision of 3.2 mm using an injector, was started in 2003. The currently anticipated problems include intraoperative crystalline lens damage [2,15], and, as postoperative complications, glaucoma [1,2,11,22], loss of corneal endothelial cells [2,6,7,22] and secondary cataract [4,10,11,15,22,24]. A trial of ICL in the USA showed a 2.1% incidence of secondary cataract [22].…”
Section: Introductionmentioning
confidence: 99%